Rancang Bangun Aplikasi Mobile Commerce Dengan Platform Android Berbasis Client Server (Studi Kasus tokobalanjo.com) - Novendra, Ryzki; Slamet, Legiman; Huda, Yasdinul (Universitas Negeri Padang, 2021)
The increase of internet and mobile technology has grown so fast, provides proper opportunities for rising up services to customers. In fact, this could mean the real services providing in real time and space. Nowadays, many business organizations has used mobile commerce technology. In these sectors, mobile commerce is not only being widely accepted but also it is being more used as a popular way of business/commerce. In this final project, developing mobile commerce aplication with Android Platform, based client-server in case studies Toko balanjo.com. The purpose of this project is to create sales and marketing products online which contains information and order process product. In this mobile commerce applications project, using CodeIgniter framework for server and android device for client. After the implementation of mobile commerce applications in this final project works so well. So that it can be implemented by tokobalanjo.com, in the promotion, sales and marketing online, and data management costumer, products, sales and marketing, and also the report data. Application design of mobile commerce in Padang based on Android will made using java programming language, Android Studio as IDE, Android SDK for Android application development. for design web-service is using PHP programming language with codeigniter framework and for design databese is using MySQL. This application will help users find the product and stuff in Padang. This application installed on Android-based handphone devices.